2010
DOI: 10.1002/cyto.a.20989
|View full text |Cite
|
Sign up to set email alerts
|

Polychromatic flow cytometry analysis of CD34+ hematopoietic stem cells in cryopreserved early preterm human cord blood samples

Abstract: During the last decades, extended characterizations were performed of human fullterm cord blood (hTCB) cells, but little information is available on human early preterm cord blood (hEPCB) hematopoietic stem cells (HSCs). In our study, we analyzed by flow cytometry 19 hEPCB and 17 hTCB samples. First, we observed that the percentage of CD34 Pos CD45 Dim cells was higher in hEPCB compared with hTCB and that it decreased during 16th-20th week of pregnancy. Within the CD34 Pos CD45 Dim population, we examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The MSCs were successfully culture-expanded from human Wharton’s jelly (hWJ-MSCs) (Figure 1) and were shown to be multipotent, since the cells were able to differentiate into adipocytes and osteocytes, which are both part of the mesoderm lineage (Figure 2). These cells highly expressed CD73, CD90, and CD105, but lacked expression of CD14, CD34, and CD45 (Figure 3), indicating the absence of contaminating hematopoietic cells in the culture [22]. In accordance with previous reports, these cells also demonstrated a lack of the co-stimulatory molecules CD80 and CD86 [23], conferring the ability to escape from immune surveillance.…”
Section: Discussionsupporting
confidence: 84%
“…The MSCs were successfully culture-expanded from human Wharton’s jelly (hWJ-MSCs) (Figure 1) and were shown to be multipotent, since the cells were able to differentiate into adipocytes and osteocytes, which are both part of the mesoderm lineage (Figure 2). These cells highly expressed CD73, CD90, and CD105, but lacked expression of CD14, CD34, and CD45 (Figure 3), indicating the absence of contaminating hematopoietic cells in the culture [22]. In accordance with previous reports, these cells also demonstrated a lack of the co-stimulatory molecules CD80 and CD86 [23], conferring the ability to escape from immune surveillance.…”
Section: Discussionsupporting
confidence: 84%
“…The results showed that PCB-CIK cells had a higher proliferation rate than the TCB-CIK cells on days 7, 8, 9 and 10. The possible cause is that preterm infant cord blood has more immature and undifferentiated cells (22). However, the PCB-CIK cells were difficult to cultivate.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published manuscripts, summarize flow cytometry characterization and specification of these stem cell based on phenotypic and differentiation stage‐specific markers, for isolation and studying their biology and clinical applications . Multiparametric flow cytometry and image stream analysis, the latter one combining morphological and imaging analysis with population‐relevant antigene expression are being used for identifying tissue‐specific stem cells, as well as for tumor cells and subpopulations within them in humans and animals .…”
Section: Surface Markers Of Hematopoietic‐ Bone Marrow‐ and Umbilicmentioning
confidence: 99%